2015
DOI: 10.1371/journal.pone.0129848
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Carboxylase Is Up-Regulated in Breast Cancer and Essential to Support Growth and Invasion of MDA-MB-231 Cells

Abstract: Pyruvate carboxylase (PC) is an anaplerotic enzyme that catalyzes the carboxylation of pyruvate to oxaloacetate, which is crucial for replenishing tricarboxylic acid cycle intermediates when they are used for biosynthetic purposes. We examined the expression of PC by immunohistochemistry of paraffin-embedded breast tissue sections of 57 breast cancer patients with different stages of cancer progression. PC was expressed in the cancerous areas of breast tissue at higher levels than in the non-cancerous areas. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 55 publications
10
99
0
Order By: Relevance
“…To test our hypothesis we employed a pCMV6 plasmid expressing PC transcript variant 1 (NM_ 000920.2) inserted downstream of the cytomegalovirus promoter (Origene, Rockville, MD). Previous studies have shown the breast cancer cells predominantly express transcript variant 1 [16], with studies in our laboratory confirming the same pattern of expression in the MCF10 cell model (data not shown). Following transfection with the PC containing pCMV6 plasmid, PC mRNA was significantly increased in MCF10CA1a at two and five days compared to the control empty pCMV6-Neo plasmid, with no significant difference between vehicle and 1,25(OH) 2 D treated cells (Figure 6A).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…To test our hypothesis we employed a pCMV6 plasmid expressing PC transcript variant 1 (NM_ 000920.2) inserted downstream of the cytomegalovirus promoter (Origene, Rockville, MD). Previous studies have shown the breast cancer cells predominantly express transcript variant 1 [16], with studies in our laboratory confirming the same pattern of expression in the MCF10 cell model (data not shown). Following transfection with the PC containing pCMV6 plasmid, PC mRNA was significantly increased in MCF10CA1a at two and five days compared to the control empty pCMV6-Neo plasmid, with no significant difference between vehicle and 1,25(OH) 2 D treated cells (Figure 6A).…”
Section: Resultssupporting
confidence: 83%
“…Since previous studies [16], as well as studies in our laboratory, confirmed that breast cancer cells predominantly express transcript variant 1, the PC transcript variant 1 (NM_ 000920.2) clone was inserted into the pCMV6-Neo vector downstream of the cytomegalovirus (CMV) immediate-early promoter. For transfection, cells were grown in either 24-well or 6-well plates to 60% confluence and transiently transfected using lipofectamine 2000 (ThermoFisher Scientific, Waltham, MA) for 20 hours according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three alternative 5′ untranslated region (5′UTR) mRNA variants are produced from the two promoters, with variant 2 transcribed from the proximal promoter while variants 1 and 3 are transcribed from the distal promoter. Previous studies demonstrated that human breast cancer cells express primarily transcript variant 1 [33]. To confirm the same pattern of expression in MCF10A- ras cells, real time-PCR analysis of cDNA was performed using three forward primers that bind to the 5′-untranslated regions (UTR) of variant 1, 2 or 3, with a common reverse primer that binds to exon 1 within the coding region to specifically amplify the three different 5′UTR variants.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting finding in the present study is the characterization of PC as a direct transcriptional target of 1,25(OH) 2 D. The distal P2 promoter, where the VDRE was identified, regulates transcription of PC in breast epithelial cells as well as pancreatic beta cells [33,38]. PC further plays an important role in glucose stimulated insulin secretion in the latter cell type [32].…”
Section: Discussionmentioning
confidence: 99%